Acute Bacterial Meningitis as an Occupational Disease - Seixas, Diana (2014)
Streptococcus suis is a zoonotic pathogen with worldwide distribution, responsible for more than 700 human cases globally reported. This infection affects mostly men, exposed to pig or pork, which leads to its usual classification as an occupational disease. We report a case of acute bacterial meningitis in a 44 years old male. According to his past medical history, the patient had alcohol consumption and worked in a restaurant as a piglet griller. Microbiological examination of blood and CSF revealed S. suis. After 14 days of ceftriaxone the patient fully recovered. The authors review the clinical reports previously described in Portugal. In all of them was possible to identify risk exposition to pork. We alert to this microorganism’s importance in Portugal where it is probably underdiagnosed.Keywords: Occupational Diseases; Occupational Exposure; Meningitis, Bacterial; Streptococcal Infections; Streptococcus suis; Portugal.